The role of indirubins in inflammation and associated tumorigenesis - Cheng, Xinlai; Merz, Karl-Heinz (Drug discovery from mother nature, 2016)
Indirubin is the major active component of an herbal recipe ‘Dangui Luhui Wan’ (当归芦荟丸) in traditional Chinese medicine (TCM). It is widely used in China for the treatment of inflammation, cancer, and other chronic diseases and is known for good efficiency and very low side effects. Primary studies on the mechanism of action revealed that indirubin and derivatives are potent ATP-competitive inhibitors of CDKs and GSK3ß achieving IC50 values down to the low nanomolar range. However, the clinical application of indirubins is limited by the extremely poor water solubility (<1 mg/L in general) and consequently the insufficient bioavailability originating from strong binding forces in the crystal lattice. In the last few decades, a lot of efforts had been put into the structure optimization of indirubin derivatives binding selectively to specific kinases. Thus, a number of new indirubins have been developed bearing substituents mainly in the 5- and 3′-position suitable for improved solubility and inhibition against CDKs and GSK3ß, referred to as canonical indirubins. Interestingly, several noncanonical 7- and 7′-indirubin derivatives have been reported, showing a distinct binding model in the ATP-binding pocket and targeting a very different spectrum of protein kinases as seen from kinase profiling. In this chapter, we will review the field of indirubin research from its discovery, synthesis, chemical modification, structure-activity relationship, and mechanism of action to molecular targets comprising recent advantages and new findings in the context of inflammation-associated signaling pathways, in particular in tumorigenesis, including NF-κB, STAT3, TGF-ß, and AhR.